The Lived-In Experience and Psychological Recount of Dog Bite Victims Visiting the Anti-Rabies Clinic in Kashmir: A Qualitative Study - Khalid Bashir; Zeenat Kausar; S. Muhammad Salim Khan; Inaamul Haq (Indian Association of Preventive and Social Medicine, 2022)
Introduction: There is a necessitated need for canvassing and prioritizing measures towards rabies elimination beyond existing statuesque post-exposure prophylaxis. Moreover, there is a need to characterize the psychological and intrusive experiences of dog-bite victims to portray a picture beyond the public health perspective. Objective: To get an expressive understanding of the psychological and lived-in experience of dog bite victims' to complement existing concepts. Method: The study was conducted at the anti-rabies clinic(ARC) of SMHS hospital which receives animal bite cases from the whole of Kashmir valley. Participants were selected purposefully based on the inclusion criteria, and data saturation was reached with eleven participant interviews. One to one in-depth interviews were conducted with eleven (11) dog bite victims, using a preformed interview guide. Data analysis was performed using Colaizzi's phenomenological method to describe the individualistic experiences faced in peculiar conditions with familiar phenomena embedded in them. Results: Data analysis yielded three overarching themes and nine subthemes viz:-1.Spiritual and emotional ineffectualness. (Suffering and affliction, Spiritual sulkiness, Emotional emergence) 2. Flashbacks of being hindered and defenseless. (Lack of focus in one's work, lacking the courage to protect, Being shaky)3. Social and economical implications. (Financial loss, group and peer detachment, preferring isolation) Conclusion: The results of this study showed that dog bite patients experience an unpleasant phenomenon in the face of being bitten by the dogs and are subjected to severe psychological pressures that require attention and support of medical professionals, psychologists and government authorities.